2022
DOI: 10.3390/ijgi11010058
|View full text |Cite
|
Sign up to set email alerts
|

Achieving ‘Active’ 30 Minute Cities: How Feasible Is It to Reach Work within 30 Minutes Using Active Transport Modes?

Abstract: Confronted with rapid urbanization, population growth, traffic congestion, and climate change, there is growing interest in creating cities that support active transport modes including walking, cycling, or public transport. The ‘30 minute city’, where employment is accessible within 30 min by active transport, is being pursued in some cities to reduce congestion and foster local living. This paper examines the spatial relationship between employment, the skills of residents, and transport opportunities, to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
(70 reference statements)
1
2
0
Order By: Relevance
“…Considering the three models of CBL, CDL, and CAL, we found that people who were residing outside Milan and had to commute to their work or other activities to the metropolitan area were, respectively, 5.4, and 3.7 times more likely to commute by private car and public transport versus active mode of transport. These results, as expected, are in line with prior studies ( Ashrafi & Neumann, 2017 ; Both et al, 2022 ; Cheng et al, 2019 ; De Vos et al, 2022 ; Yu et al, 2019 ). In the second model, related to the choice of transport mode during the lockdown, these explanatory variables show a different relation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering the three models of CBL, CDL, and CAL, we found that people who were residing outside Milan and had to commute to their work or other activities to the metropolitan area were, respectively, 5.4, and 3.7 times more likely to commute by private car and public transport versus active mode of transport. These results, as expected, are in line with prior studies ( Ashrafi & Neumann, 2017 ; Both et al, 2022 ; Cheng et al, 2019 ; De Vos et al, 2022 ; Yu et al, 2019 ). In the second model, related to the choice of transport mode during the lockdown, these explanatory variables show a different relation.…”
Section: Discussionsupporting
confidence: 93%
“…Longer commutes can cause traffic congestion, and using motorised vehicles. While, compact cities can foster shorter daily travel time and consequently encourage the use of active modes ( Both et al, 2022 ). Besides, some individual (socio-demographics) characteristics such as gender, age, income, and availability or possession of transport mode significantly determine travel mode behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Noting that short trips were defined as journeys lasting 30 minutes or less. This definition aligns with typical durations for active transportation modes like walking, cycling, and micro-mobility, focusing on urban travel patterns (Both et al, 2022).…”
Section: Methodology 31 Data Collectionmentioning
confidence: 92%
“…Considering indicators such as flow, transfer or trip features (e.g., trip time, transfer location), studies have been able to identify mobility patterns and travel preferences, for instance: de Magalhães et al [33] say that comfort, direct lines and decrease travel time are key factors to create attractiveness for commuting private users and they are willing to walk around 500 m to transfers; Espino et al [36] analyse travel preferences and suggest that, from a policy point of view, decrease travel time and the transfer cost encourages the use of bus transport system. Indeed, the assessment of these statistical indicators has been pivotal to aiding the operators' planning, help redesigning the network (e.g., 30 min city or even 15 min city projects), and increasing the public transport attractiveness, especially for private car users [37][38][39].…”
Section: Transfer and Trip Status Indicatorsmentioning
confidence: 99%